The conditions and requirements of the values to establish the world order (Journal of Philosophy Culture and Political Science, 2018)
This article discusses the transformation of the idea of world order in the sphere of geopolitics to the philosophy, the essence of globalization and the phenomenon, describing its latest results. The analysis of the current spiritual state of Kazakhstan gives opportunity to make conclusion about substantial inconsistencies encountered in the course of a gradual acceptance by the local population of the positive achievements of Western culture. In this regard, it is possible to express the opinion that poorly developed public environment will not achieve the social cultural achievements of the economically and culturally progressive advanced society by means of conventional copying it. Along with this refers to the fact that the inner outlook and positive personal idea of development as a characteristic, day after day turn into an actual problem. The research achieved the following results: philosophical analysis on the problem of world order, socio-cultural continuity reveals not only the significance of motives, but also people’s worldview of these motifs and allows you to fully discover the essence of these social sources, as the injustices, philosophical and good looking. There is another world order that is unlike thepresent world order, it dramatically influences the fate of a person can change the world and destroy theold world order, it will be set to the result of the influence of ordered events and facts. You can be surethat today’s new world order – a phenomenon arising out of complex contradictions and destructionof collisions of interests of the leading actors of world politics. To establish a new world order of Statesshould act in the world, without clashing with each other, and its Foundation is certainly the principle oftolerance, importance of tolerance.Key words: society, globalization, world order, value, continuity, culture, tolerance, tradition, people.